Própolis vermelha brasileira: ação antibacteriana contra patógenos endodônticos e avaliação in vitro da produção de radicais livres - Oliveira Neto, Nilson Ferreira de (2021)
Maintenance of pulp vitality is one of the purposes of vital pulp therapies (VPT) and selection of a good material strongly affects the long-term outcomes. Brazilian red propolis (BRP) is a great antimicrobial agent and may provide therapeutic solutions for pulp therapy. We hypothesized that BRP could show promising antibacterial activity and perform similar behavior with Mineral Trioxide Aggregate (MTA) in free radicals production and cell viability findings. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of BRP was determined against anaerobic endodontic pathogens. Human dental pulp fibroblasts (HDPFs) were seeded in 96 well-plates and exposed, after 24h, to BRP10 (10 μg/mL), BRP50 (50μg/mL), MTA extracts (1:1, 1:2, 1:4 e 1:8), dimethyl sulfoxide 0,5 % (DMSO) and cell culture medium (DMEM). Subsequently, 24h after the exposure to materials, the groups were tested for cell viability (MTT formazan assay), and free radicals production (reactive oxygen species - ROS, 2’,7’-dichlorodihydrofluorescein diacetate fluorescent probe (DCFHDA) and nitric oxide – NO, Griess reagent). The One-way ANOVA and Tukey’s tests were employed considering significance level of 5%. MIC/MBC values of BRP performing antibacterial activity for P. micra (6.25/6.25 μg/mL), F. nucleatum (25/25 μg/mL), P. melaninogenica (50/100 μg/mL), P. nigrescens (50/100 μg/mL), P. intermedia (50/100 μg/mL) and P. gingivalis (50/200 μg/mL). In our cell viability findings, BRP and MTA were able to stimulate cell viability, emphasizing BRP10 and MTA 1:8 (p=0.007 and p=0.001, respectively). Furthermore, it was observed that MTA 1:1, MTA 1:2 and BRP50 slightly increased ROS (p<.001) and NO production (p=0.008, p=0.007 and p<.001 respectively) compared to DMEM group. On the other hand, BRP10 did not raised the amount of ROS (p=0.976) and NO (p=0.974) production compared to DMEM. Therefore, BRP presented high antibacterial activity for anaerobic bacteria involved in primary endodontic infection and, both BRP and MTA promoted the viability of HDPFs without greatly increased NO and ROS production.